UPAYA PENINGKATAN HASIL TANGKAPAN CACING KAPAL Bactronophorus sp. DARI EKOSISTEM BAKAU - DENNY SYAPUTRA (Akuatik: Jurnal Sumberdaya Perairan, 2007)
Shipworm is specialized as wood borer bivalve.They has a pair of shell which reduce to a small but highly efficient cutting organ at the extreme anterior end by which they bore the woods up to 19 mm a day. Shipworm derives some nutrition from the wood that they swallow with enzymatic mechanizm and bacterial simbionts. They store their products of digestion in the form of glycogen and fat. Mangrove is their natural habitat, and they also play an important ecological role in the reduction of mangrove woods. Syaputra (2003) has reported that shipworm which lives in Mangrove ecosystem near Tanjung Batu Village is from genus Bactronophorus. It is based on Allan (1962) who said that shipworm with stilt-like pallets, short siphons and the shell with 1.85 cm of length, and total length of pallet reaches 5 cm is Bactronophorus. As the other fisheries coomodities (crabs, shrimps, etc), shipworm could be an alternative source of health food by providing the essential fatty acids. Until now, we still have to catch the shipworm from nature, so that, the yields would be depend on the carrying capacity, catch per unit area, and catch season. For the future, it is important for the stakeholders altogether assuring that our mangrove ecosystem still provides nursery and feeding ground function especially for the shipworm.